Boa Companhia e a composição de Primus: “encontros” que geram procedimentos criativos - Daves Otani (Pitágoras 500, 2013)
The article talks about chance as a decisive element regarding the direction of the construction process of the play Primus, by the group Boa Companhia, as well as the company's creative attitude and how their history provides that "chance encounters" generate ways of adapting the Franz Kafka’s short story (A Report to an academy), which inspired the play. As an example, the author speaks about how capoeira was used throughout the play as a result of the group's own history in the State University of Campinas (Unicamp), the history of capoeira in the Department of Performing Arts, where the group was formed, and the approach of the artistic director and the repertoire company, which add elements based on "chance encounters".